Reaching the Urban and Farm Press With Agricultural News-features - Bud Gavitt (Journal of Applied Communications, 1983)
In January 1983 we surveyed Connecticut newspaper editors and U.S. farm newspaper editors on their preference and possible use of four news-features on various agricultural topics.